Students’ Feedback on Vlogging as an Educational Tool in Probability and Statistics: A Qualitative Study - Arnel Travero; Angelie T Padilla (Universitas Sarjanawiyata Tamansiswa, 2025)
This qualitative study explores students' feedback on the use of vlogging as an educational tool in Probability and Statistics. Using a phenomenological approach, the study gathered insights from Grade 12 students through semi-structured interviews, which were analyzed using thematic analysis. Results revealed that students faced cognitive and technical challenges, including pre-vlog preparation difficulties, editing constraints, limited access to high-quality gadgets, and time management issues. Despite these challenges, students reported that vlogging enhanced their appreciation of mathematics, fostered active learning, and developed their independence and problem-solving skills. Vlogging encouraged students to bridge mathematical concepts to real-world applications, shifting their perception of mathematics from a memorization-based subject to a meaningful and engaging learning experience. Additionally, vlogging promoted student autonomy, as learners took responsibility for structuring their explanations and overcoming technical difficulties. Given these findings, the study recommends integrating vlogging as an educational tool to complement traditional mathematics instruction. Educators should provide structured guidance, access to resources, and strategies for time management to maximize its benefits. Future research may explore the long-term effects of vlogging on mathematical confidence, self-regulated learning, and academic performance. Vlogging presents a promising pedagogical approach that enhances student engagement, conceptual understanding, and mathematics appreciation.